A Virtual Ethnography Study: Fandom and Social Impact in Digital Era - Ade Kusuma; Adiasri Putri Purbantina; Vina Nahdiyah; Ucik Uswatun Khasanah (ETNOSIA : Jurnal Etnografi Indonesia, 2020)
Along with the advancement of Information and Communications Technology, the internet plays a massive role in South Korean idol groups' rapid growth. Global fans quickly become one of the crucial elements that heavily influence idol groups’ global popularity. BTS Army is one of the largest music fandoms in the past several years. This research analyzes fan culture using the case of BTS Army community in Surabaya. This research employs a qualitative method under a virtual ethnographic approach. This research conducts participant observation, in-depth interviews, focus group discussions, literature studies, and documentation on collecting the data. This research finds that online media provides a space for the mem Army community in members Surabaya to actively interact with each other as they share ideas and discussions over various BTS activities. The online interaction also leads to offline activities (e.g., regular fan-meetings, BTS members’ birthday celebrations, and other social activities). The research concludes that global fandom also acts as social agents. The observation of the BTS Army community in Surabaya shows that BTS’s charity works (e.g., Love Yourself campaign) influence the fans to be more involved in various social movements such as hosting multiple charity events.